2010
DOI: 10.1007/s10327-010-0234-5
|View full text |Cite
|
Sign up to set email alerts
|

First report of two distinct badnaviruses associated with Bougainvillea spectabilis in India

Abstract: Two distinct types of symptoms, severe yellow mosaic and chlorotic vein-banding, were observed on Bougainvillea spectabilis at two different locations in India. Electron microscopy revealed bacilliform virus particles in leaf samples from both places. PCR amplification, cloning, sequencing and sequence analysis of reverse transcriptase and ribonuclease H coding region in open reading frame 3 indicated that two distinct badnaviruses are associated with B. spectabilis in India.Keywords Badnavirus Á Bougainvillea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…As a monophyletic group formed by Brazilian isolates 25(02), 28(02), 35(01) and Delhi, India (GQ254411), isolate was supported by 100% bootstrap, they can be considered the same species, as proposed by Baranwal et al. (). The authors also suggested a new species called Tirupati, which was not found in the samples tested in this study.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…As a monophyletic group formed by Brazilian isolates 25(02), 28(02), 35(01) and Delhi, India (GQ254411), isolate was supported by 100% bootstrap, they can be considered the same species, as proposed by Baranwal et al. (). The authors also suggested a new species called Tirupati, which was not found in the samples tested in this study.…”
Section: Resultsmentioning
confidence: 54%
“…In a previous study, Baranwal et al. () also reported diversity in nucleotide sequences of badnaviruses in bougainvillea from two different geographical regions of India (Delhi and Tirupati). Based on the nucleotide sequence identity within the RT/RNase H, whose value was lower than 80% (King et al.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations